2022
DOI: 10.3389/fnhum.2022.744487
|View full text |Cite
|
Sign up to set email alerts
|

Past and Future Explanations for Depersonalization and Derealization Disorder: A Role for Predictive Coding

Abstract: Depersonalization (DP) and derealization (DR) refer to states of dissociation in which one feels a sense of alienation in relation to one’s self and environment, respectively. Whilst transient episodes often diminish without treatment, chronic experiences of DP and DR may last for years, with common treatments lacking a strong evidence base for their efficacy. We propose a theoretical explanation of DP and DR based on interoceptive predictive coding, and discuss how transient experiences of DP and DR may be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 120 publications
1
6
0
Order By: Relevance
“…Our model represents a theoretical and computational advance of previous conceptualisations (e.g., 63 ) within an active inference framework. In line with Gatus and colleagues 10 we propose that DPD arises as a consequence of the suppression of interoceptive signals (deemed unreliable) whilst other sensory modalities remain intact. As illustrated by our simulation, to account for the prediction errors generated by incoherent streams of information, multisensory integration processes rely on sensory input from modalities other than interoception (e.g., exteroception, proprioception).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our model represents a theoretical and computational advance of previous conceptualisations (e.g., 63 ) within an active inference framework. In line with Gatus and colleagues 10 we propose that DPD arises as a consequence of the suppression of interoceptive signals (deemed unreliable) whilst other sensory modalities remain intact. As illustrated by our simulation, to account for the prediction errors generated by incoherent streams of information, multisensory integration processes rely on sensory input from modalities other than interoception (e.g., exteroception, proprioception).…”
Section: Discussionsupporting
confidence: 85%
“…Several attempts to explain the aetiology of DPD have been made in recent years 10 . One model, developed by Sierra and David 11 , suggests that DPD may arise as a consequence of an increased cognitive control of the subjective affective experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the International Society for the Study of Trauma and Dissociation ( 2011a , b ), five symptoms of dissociation can be identified: depersonalization, derealization, dissociative amnesia, identity confusion, and identity alteration (Sar, 2014 ). Depersonalization can be described as the sense of being detached from or not feeling in one's body, and it can represent what is often referred to as an “out-of-body” experience (Guralnik et al, 2000 ; Simeon et al, 2001 ; Gatus et al, 2022 ). Derealization is the sense of feeling detached from the world or the sense of the world not being real.…”
Section: Introductionmentioning
confidence: 99%
“…Derealization is the sense of feeling detached from the world or the sense of the world not being real. It can be an association with a description of the world as being phony, foggy, far away, or as if seen through a veil (Steinberg and Steinberg, 1995 ; Gatus et al, 2022 ). Dissociative amnesia can be described as the inability to recall relevant autobiographical information that is not related to ordinary oblivion.…”
Section: Introductionmentioning
confidence: 99%